Faculty-instructional designer partnerships in higher education - Poff, Nicole Frances (My University, 2026)
The expansion of online learning in higher education has increased the need for collaboration between faculty and instructional designers during the course development process. While instructional designers frequently support faculty in course design, pedagogy, and technology integration, less is known about how faculty perceive these collaborative relationships. The purpose of this mixed-methods study was to examine faculty perceptions of collaboration with instructional designers in the development of online courses and to explore the factors that shape these collaborative experiences. Guided by Role Theory, this study employed a mixed-methods design integrating quantitative survey data and qualitative interview data. Quantitative data were collected using the Perception of Interprofessional Collaboration Model Questionnaire (PINCOM-Q) to examine faculty perceptions across domains, including communication, role expectations, and organizational support. Qualitative data was gathered through semi-structured interviews with faculty who had collaborated with instructional designers in developing online courses. Findings indicated that faculty generally perceived collaboration with instructional designers positively, particularly regarding communication and professional support. Qualitative analysis further revealed that collaboration experiences were shaped by role clarity, communication practices, institutional context, and workload constraints. The findings suggest that collaboration between faculty and instructional designers functions as a process of negotiating professional roles within institutional course development structures. This study contributes to the literature on online course development by highlighting the importance of clear role expectations, effective communication, and supportive institutional structures in fostering productive faculty–instructional designer partnerships.
Keywords: Instructional designer; Online course development; Higher education; Faculty course design; Instructional designer collabortion; Faculty collaboration